Undifferentiated Pleomorphic Sarcoma of the Male Breast Causing Diagnostic Challenges - Jeong, Young Ju (Korean Breast Cancer Society, 2011)
Undifferentiated pleomorphic sarcoma of the breast are uncommon and often present diagnostic challenges. Herein, we report a case of the undifferentiated pleomorphic sarcoma occurring in the male breast. A 76-year-old man presented with a palpable bean-sized mass in his left breast for two months. Core needle biopsy revealed the presence of atypical cells in a fibrous proliferative lesion, which was removed by wide excision. Based on examination of the excised tumor, the initial pathologic diagnosis was atypical spindle cell lesion with uncertain malignant potential. One year later, the patient returned with a recurrent mass atthe previous surgical site. The mass was again surgically removed using wide excision. Based on histological findings with immunomarkers, the final diagnosis was undifferentiated pleomorphic sarcoma. Undifferentiated pleomorphic sarcoma of the breast can cause genuine diagnostic difficulty and appropriate immunohistochemistry is mandatory for differential diagnosis.